Impact of 3D printing technology for the construction of a prototype of low-cost robotic arm prostheses - Maxwell Salazar; Ricardo Rosero; Oscar Zambrano; Paola Portero (Advances in Mechanical Engineering)
This article explores the impact of 3D printing technology on prototyping low-cost robotic arm prosthetic. The research begins with a thorough analysis of the robotic arms currently available on the market, with the aim of identifying their characteristics, costs, and limitations. Based on this review, an in-house design is developed using simplified CAD software, tailored to optimize both functionality and production efficiency. The construction of the prototype is carried out using 3D printing, taking advantage of the capabilities of this technology to reduce costs and manufacturing times compared to traditional methods. The article details the design and printing process, highlighting key decisions made to maximize the economic viability of the project. Finally, a detailed analysis of the costs associated with the project is carried out, comparing the results obtained with the initial reference data. This analysis allows us to evaluate the effectiveness of 3D printing as a low-cost solution in the development of robotic prostheses, highlighting its economic benefits and potential areas for improvement. The findings suggest that 3D printing represents a promising alternative for the creation of accessible robotic prosthetic, with significant implications for cost reduction and democratization of access to new technologies.